Here's the question you clicked on:
abbie1
Please help!! If you were to use the substitution method to solve the following system, choose the new system of equations that would result if x was isolated in the third equation. 2x - 3y + z = -4 2x - 2y + z = -1 x - 2y + 3z = -6
replace \(x\) everwhere you see it in the top two equations by \(2y-3z-6\)
ok for the first i got y-5z=8
first one would simplify to \(2y-5z=8\)
yeah ok you got the idea
then once get all those what do i do??
or is those the final answers?? do you have to combine??
do it for the next equation just like you did for the first one you get \(2y-5z=11\)
ok 2nd is 2y-11z-12 and 3rd is -6=-6
that will give you the new system \[2y-5z=8\] \[2y-5z=11\]
btw this system has no solution